2022
DOI: 10.1007/978-3-030-79353-1_6
|View full text |Cite
|
Sign up to set email alerts
|

Advancement of Efficiency Evaluation for Healthcare

Abstract: The objective of this chapter is to provide conceptual understandings of evaluation methods for healthcare and concrete illustrations in order to take stock of the advancements and applications on the subject. The chapter is divided in four sections: the first one sets the stage at a European level by evaluating healthcare system performance; the second goes back to the fundamental principles of methods of evaluation for healthcare; the third one follows with illustrations of patient-centred and person-centred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Therefore, review of recent publications found the following issues, which will be considered in this study: The study of medical staff's perception of involvement in adverse events can be organised using special questionnaires that should consider various kinds of mental distresses of second victims to figure out how deep their distresses are; The sample of the examined potential second victims should be divided into categories, including medical professions, experience, age, and gender, to find out whether this is the same problem for all healthcare professionals; Given the wide range of medical professions experiencing the problem of second victims, an expanded sample of representatives of various departments of the surveyed hospital should be considered, including COVID department, gynaecology department, etc. Given the importance of not only measuring the depth of the problem, but also understanding how to solve it, makes it reasonable to include points in the questionnaire related to previous experience of overcoming the consequences of adverse events examined by medical staff. Moreover, the implementation of the Danish Second Victim Support Program proposed by Schrøder et al 31 may cause difficulties on the European continent as it is not homogeneous. For example, in countries such as Sweden or Ireland, which have high healthcare performance, 34 similar programs have already been implemented and are not difficult to implement there. On the other hand, in countries with low performing healthcare systems such as Bulgaria or Ukraine, 35 the implementation of such programs may be difficult.…”
Section: Review Of the Second Victim Phenomenonmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, review of recent publications found the following issues, which will be considered in this study: The study of medical staff's perception of involvement in adverse events can be organised using special questionnaires that should consider various kinds of mental distresses of second victims to figure out how deep their distresses are; The sample of the examined potential second victims should be divided into categories, including medical professions, experience, age, and gender, to find out whether this is the same problem for all healthcare professionals; Given the wide range of medical professions experiencing the problem of second victims, an expanded sample of representatives of various departments of the surveyed hospital should be considered, including COVID department, gynaecology department, etc. Given the importance of not only measuring the depth of the problem, but also understanding how to solve it, makes it reasonable to include points in the questionnaire related to previous experience of overcoming the consequences of adverse events examined by medical staff. Moreover, the implementation of the Danish Second Victim Support Program proposed by Schrøder et al 31 may cause difficulties on the European continent as it is not homogeneous. For example, in countries such as Sweden or Ireland, which have high healthcare performance, 34 similar programs have already been implemented and are not difficult to implement there. On the other hand, in countries with low performing healthcare systems such as Bulgaria or Ukraine, 35 the implementation of such programs may be difficult.…”
Section: Review Of the Second Victim Phenomenonmentioning
confidence: 99%
“…Moreover, the implementation of the Danish Second Victim Support Program proposed by Schrøder et al 31 may cause difficulties on the European continent as it is not homogeneous. For example, in countries such as Sweden or Ireland, which have high healthcare performance, 34 similar programs have already been implemented and are not difficult to implement there. On the other hand, in countries with low performing healthcare systems such as Bulgaria or Ukraine, 35 the implementation of such programs may be difficult.…”
Section: Review Of the Second Victim Phenomenonmentioning
confidence: 99%
See 1 more Smart Citation